Beam control system and output fine-tuning for safe and precise delivery of FLASH radiotherapy at a clinical linear accelerator - Konradsson, Elise; Wahlqvist, Pontus; Thoft, Andreas; Blad, Börje; Bäck, Sven; Ceberg, Crister; Petersson, Kristoffer (Frontiers in Oncology, 2024)
Introduction We have previously adapted a clinical linear accelerator (Elekta Precise, Elekta AB) for ultra-high dose rate (UHDR) electron delivery. To enhance reliability in future clinical FLASH radiotherapy trials, the aim of this study was to introduce and evaluate an upgraded beam control system and beam tuning process for safe and precise UHDR delivery. Materials and Methods The beam control system is designed to interrupt the beam based on 1) a preset number of monitor units (MUs) measured by a monitor detector, 2) a preset number of pulses measured by a pulse-counting diode, or 3) a preset delivery time. For UHDR delivery, an optocoupler facilitates external control of the accelerator’s thyratron trigger pulses. A beam tuning process was established to maximize the output. We assessed the stability of the delivery, and the independent interruption capabilities of the three systems (monitor detector, pulse counter, and timer). Additionally, we explored a novel approach to enhance dosimetric precision in the delivery by synchronizing the trigger pulse with the charging cycle of the pulse forming network (PFN). Results Improved beam tuning of gun current and magnetron frequency resulted in average dose rates at the dose maximum at isocenter distance of >160 Gy/s or >200 Gy/s, with or without an external monitor chamber in the beam path, respectively. The delivery showed a good repeatability (standard deviation (SD) in total film dose of 2.2%) and reproducibility (SD in film dose of 2.6%). The estimated variation in DPP resulted in an SD of 1.7%. The output in the initial pulse depended on the PFN delay time. Over the course of 50 measurements employing PFN synchronization, the absolute percentage error between the delivered number of MUs calculated by the monitor detector and the preset MUs was 0.8 ± 0.6% (mean ± SD). Conclusion We present an upgraded beam control system and beam tuning process for safe and stable UHDR electron delivery of hundreds of Gy/s at isocenter distance at a clinical linac. The system can interrupt the beam based on monitor units and utilize PFN synchronization for improved dosimetric precision in the dose delivery, representing an important advancement toward reliable clinical FLASH trials.